PROBIOTICS - YESTERDAY, TODAY, TOMORROW - L.N. Tsvetkova ("Paediatrician" Publishers LLC, 2006)
The article deals with the modern view on the probiotics' role in treatment and prevention of various infant diseases. The author describes a classification of probiotics, dosage and terms of their application.Key words: microecological internal environment, dysbacteriosis, children, probiotics, classification.